Extracellular microRNAs and endothelial hyperglycaemic memory: a therapeutic opportunity?. Issue 9 (22nd June 2016) - Prattichizzo, F.; Giuliani, A.; De Nigris, V.; Pujadas, G.; Ceka, A.; La Sala, L.; Genovese, S.; Testa, R.; Procopio, A. D.; Olivieri, F.; Ceriello, A.
Abstract : Type 2 diabetes mellitus (T2DM) is a major cause of cardiovascular (CV) disease. Several large clinical trials have shown that the risk for patients with diabetes of developing CV complications is only partially reduced by early, intensive glycaemic control and lifestyle interventions, and that such complications result from changes in complex, not fully explored networks that contribute to the maintenance of endothelial function. The accumulation of senescent cells and the low‐grade, systemic, inflammatory status that accompanies aging (inflammaging) are involved in the development of endothelial dysfunction. Such phenomena are modulated by epigenetic mechanisms, including microRNAs (miRNAs). MiRNAs can modulate virtually all gene transcripts. They can be secreted by living cells and taken up in active form by recipient cells, providing a new communication tool between tissues and organs. MiRNA deregulation has been associated with the development and progression of a number of age‐related diseases, including the enduring gene expression changes seen in patients with diabetes. We review recent evidence on miRNA changes in T2DM, focusing on the ability of diabetes‐associated miRNAs to modulate endothelial function, inflammaging and cellular senescence. We also discuss the hypothesis that miRNA‐containing extracellular vesicles (i.e. exosomes and microvesicles) could be harnessed to restore a 'physiological' signature capable of preventing or delaying the harmful systemic effects of T2DM.